Uptake and retrograde axonal transport of horseradish peroxidase (HRP) injected into botulin-poisoned muscle in rats (author's transl) - Tian Wen-hao (Acta Pharmacologica Sinica, 2016)
The quantity of HRP in sciatic nerve and both ventral and dorsal roots of L4-6 spinal segments of rats was determined by coupled oxidation reaction method. Little endogenous peroxidase was found in normal nerve tissue. After HRP was injected into gastrocnemius muscle, HRP was detected not only in the sciatic nerve, but also in the ventral and dorsal roots. Histochemical study confirmed that retrograde axonal transport of HRP proceeded mainly in the axon. No significant difference in the HRP quantities was found between poisoned and normal rats. The HRP quantities in the nerve tissues of both groups of rats were increased by stimulating the nerve. These results suggest that the uptake and retrograde transport of HRP in neuro-muscular junctions are not restricted to axonal terminals but occurred mainly at some preterminal portions up to the tips of the terminals.